2021
DOI: 10.7717/peerj.10942
|View full text |Cite
|
Sign up to set email alerts
|

Differences between adjusted vs. non-adjusted loads in velocity-based training: consequences for strength training control and programming

Abstract: Strength and conditioning specialists commonly deal with the quantification and selection the setting of protocols regarding resistance training intensities. Although the one repetition maximum (1RM) method has been widely used to prescribe exercise intensity, the velocity-based training (VBT) method may enable a more optimal tool for better monitoring and planning of resistance training (RT) programs. The aim of this study was to compare the effects of two RT programs only differing in the training load presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 49 publications
(71 reference statements)
2
25
0
Order By: Relevance
“…This study showed statistically significant effects in full and parallel squat, but not in half squat. These findings are consistent with the fact that most of the studies reviewed have found positive results in full squat after a VBRT program [ 22 , 29 , 30 , 38 , 39 , 40 , 53 , 55 , 60 , 62 , 65 , 66 , 67 ].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This study showed statistically significant effects in full and parallel squat, but not in half squat. These findings are consistent with the fact that most of the studies reviewed have found positive results in full squat after a VBRT program [ 22 , 29 , 30 , 38 , 39 , 40 , 53 , 55 , 60 , 62 , 65 , 66 , 67 ].…”
Section: Discussionsupporting
confidence: 88%
“…However, after evaluating the abstracts, full-texts, and analyzing the strict fulfillment of the other inclusion criteria, 236 articles were excluded. A total of 22 studies met the pre-established requirements [ 22 , 29 , 30 , 38 , 39 , 40 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. Considering that the present systematic review is reported according to the parameters established in the PRISMA guidelines, a flow chart of the literature search is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations